Comparison of collagen and gelatin extracted from the skins of Nile tilapia (Oreochromis niloticus) and channel catfish (Ictalurus punctatus). (1st March 2016) - Zhang, Qiang; Wang, Qianqian; Lv, Shun; Lu, Jianfeng; Jiang, Shaotong; Regenstein, Joe M.; Lin, Lin
Abstract: Large numbers of Nile tilapia and channel catfish are processed in China providing a steady source of fish skins for the production of collagen and gelatin. Acid-soluble collagen (ASC), pepsin-soluble collagen (PSC), and gelatin (GT) were extracted from the skins of both species, and their physical and chemical properties were compared. SDS-PAGE suggested that the collagen contained two α1-chains and one α2-chain. FTIR spectra showed that the triple helical structure of ASC and PSC were more intact than that of GT. Rheological measurement and melting processes suggested that the extraction processing can significantly affect the viscoelastic properties and thermal stability of collagen and gelatin. The scanning electron microscopy showed that the interconnectivity of PSC and GT were better than that of ASC. Further work is needed to determine the potential of these materials as an alternative to mammalian-derived collagen and gelatin in applications in foods, cosmetics, and medicine.